Analisis Laju Pertumbuhan dan Efektivitas Penerimaan Retribusi Pengujian Kendaraan Bermotor pada Dinas Perhubungan Kabupaten Malang - Rizkya Noviana Romadhona; R.M Mahrus Alie; Angguliyah Rizqi Amaliyah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to analyze the growth rate and effectiveness of motor vehicle testing levy revenues at the Malang Regency Transportation Agency during the period 2020 to 2024. The approach used is quantitative descriptive with data collection techniques in the form of secondary documentation and direct interviews with related parties. The results of the study show that the average growth rate of levy revenues reached 6.83%, which is included in the positive growth category and is classified as "prime" and "developing" based on the regional levy potential matrix. This finding indicates that the motor vehicle testing levy sector is one of the important pillars in supporting Regional Original Income (PAD). However, the effectiveness of its receipts has fluctuated quite significantly, especially in 2023 and 2024 which only recorded an effectiveness of 22%. This sharp decline indicates an imbalance between the targets set and the realization of achievements in the field. Factors such as inaccurate target estimates, regulatory changes, and decreased activity after the pandemic can be the main causes. Therefore, policy evaluation and adjustment of planning strategies are needed so that levy revenues can continue to be increased sustainably and optimally.